Effectiveness of Instagram Learning Media on Chemical Equilibrium Material on Learning Outcomes of Class XI Students of SMAN 1 Payakumbuh - Alfathunnisa, Salwa; Suryelita, Suryelita (Journal of Educational Sciences, 2024)
Chemical equilibrium is one of the materials studied in class XI SMA / MA. This material is abstract and a lot of mathematical calculations, learning media is needed that can support the learning process and understanding of the concepts of students so that learning outcomes increase. Instagram learning media is available on chemical equilibrium material with valid and very practical categories but has not been tested for effectiveness. This study aims to test the effectiveness of Instagram learning media on student learning outcomes. The type of research used was pre - experimental with a one group pretest - posttest design using purposive sampling. The results showed that the percentage of N-Gain was 72% with a fairly effective category, meaning that Instagram learning media was effective enough to be used in the learning process so that it could improve the learning outcomes of students in class XI SMA N 1 Payakumbuh.